Proceedings of the 4th ACM International Workshop on Mobility Management and Wireless Access 2006
DOI: 10.1145/1164783.1164793
|View full text |Cite
|
Sign up to set email alerts
|

Sink mobility protocols for data collection in wireless sensor networks

Abstract: In wireless sensor networks data propagation is usually performed by sensors transmitting data towards a static control center (sink). Inspired by important applications (mostly related to ambient intelligence) and as a first step towards introducing mobility, we propose the idea of having a sink moving in the network area and collecting data from sensors. We propose four characteristic mobility patterns for the sink along with different data collection strategies. Through a detailed simulation study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 12 publications
0
83
0
2
Order By: Relevance
“…In a pull strategy, a node forwards its data only when the sink initiates a request for it, whereas in a push strategy a node proactively sends its data towards the sink. Chatzigiannakis et al have shown in [26] that random sink mobility can be used to reduce Emax and Ebar compared to the case of a static sink. Single hop data collection leads to the strongest reduction of energy consumption, because no data relaying load on the sensor nodes exists.…”
Section: Random Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a pull strategy, a node forwards its data only when the sink initiates a request for it, whereas in a push strategy a node proactively sends its data towards the sink. Chatzigiannakis et al have shown in [26] that random sink mobility can be used to reduce Emax and Ebar compared to the case of a static sink. Single hop data collection leads to the strongest reduction of energy consumption, because no data relaying load on the sensor nodes exists.…”
Section: Random Mobilitymentioning
confidence: 99%
“…Controlled mobility refers to schemes where sink mobility is controlled or guided based on a parameter of interest, such as residual energy of the nodes, or on a predefined objective function, or on predefined observable events [26]. A mobile sink with energy conscious approach tries to stay away from the nodes with less residual energy and tries to be in the vicinity of those nodes that have high residual energy.…”
Section: Controlled Mobilitymentioning
confidence: 99%
“…Reference [5] proposes mobility patterns for the sink and takes the advantage of sink's mobility to prolong the lifetime of the network. In [6] and [7], it is proven that that mobile sink node improves the lifetime of the network.…”
Section: Related Workmentioning
confidence: 99%
“…In [4], sink node is repositioned to enhance the performance metrics. Other related studies [5]- [9] are proposed to prolong the lifetime of the network or to reduce the energy consumption in routing. However, as the network size grows, the length of the constructed paths will increase, causing the problem described above more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Movement of the sink can follow different types of pattern in a given geographical area such as random, predetermined/fixed path or controlled movement, in order to improve the life time of WSNs. In Chatzigiannakis et al (2006), authors described a single sink WSNs uses a pull strategy to collect data from SNs. The main disadvantage of single sink is its poor coverage.…”
Section: Introductionmentioning
confidence: 99%